2016
DOI: 10.1007/s11682-016-9524-7
|View full text |Cite
|
Sign up to set email alerts
|

Altered modular organization of intrinsic brain functional networks in patients with Parkinson’s disease

Abstract: Although previous studies reported altered topology of brain functional networks in patients with Parkinson's disease (PD), the modular organization of brain functional networks in PD patients remains largely unknown. Using the resting-state functional MRI (R-fMRI) and graph theory, we examined the modular organization of brain functional networks in 32 unmedicated patients with early-to-mid motor stage PD and 31 healthy controls. Compared to the controls, the PD patients tended to show decreased integrity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 69 publications
3
22
0
Order By: Relevance
“…Regarding global topologic properties, clustering coefficient, global efficiency, and local efficiency were decreased whereas characteristic path length was increased in patients with PD compared with HC participants, which suggested that the networks in patients with PD were less locally specialized and less globally integrated. These results are consistent with recent structural and functional connectome studies (27,28) in which brain networks of early-to-mid clinical stage PD showed decreased local specialization and global integration. However, others (8) report decreased local specialization (indicated by decreased clustering coefficient and local efficiency) and maintained global integration in the brain functional network of early-stage PD.…”
Section: Figuresupporting
confidence: 92%
“…Regarding global topologic properties, clustering coefficient, global efficiency, and local efficiency were decreased whereas characteristic path length was increased in patients with PD compared with HC participants, which suggested that the networks in patients with PD were less locally specialized and less globally integrated. These results are consistent with recent structural and functional connectome studies (27,28) in which brain networks of early-to-mid clinical stage PD showed decreased local specialization and global integration. However, others (8) report decreased local specialization (indicated by decreased clustering coefficient and local efficiency) and maintained global integration in the brain functional network of early-stage PD.…”
Section: Figuresupporting
confidence: 92%
“…Lower FA characteristic path length and higher FA global efficiency are network metrics that describe greater network integration (Bullmore and Sporns, 2012). Previous studies have also shown a relationship between these global network metrics and neurocognitive function in persons with neurodegenerative disorders (Chang et al, 2016; Ma et al, 2017). It may be that higher neurocognitive function reflects increased integration within the structural brain network.…”
Section: Discussionmentioning
confidence: 73%
“…No components significantly differed between groups during the No‐RAS or Fast tapping conditions. The results indicate that within‐network correlations were overall more strongly modulated by task conditions for Controls than for the PD group, which is consistent with studies that have found lower within network connectivity and decreased modular integrity in PD during the resting state (Zhang et al ., ; Ma et al ., ).…”
Section: Resultsmentioning
confidence: 97%